1956
DOI: 10.1002/jsfa.2740071208
|View full text |Cite
|
Sign up to set email alerts
|

Nutritive value of leaf protein concentrates. II.

Abstract: Leaf protein concentrates were treated in various ways in an attempt to improve their nutritive value, as measured by the “gross protein value” technique with chicks. Washing with hot water improved the value of some lucerne concentrates by removing a water‐soluble toxic factor. No appreciable improvement was obtained by: (a) varying pH of precipitation of curd, (b) different methods of drying the wet curd, or (c) solvent extraction of pigments, waxes, etc. Dried whole juice and alkali‐soluble protein had low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
13
1

Year Published

1957
1957
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 5 publications
1
13
1
Order By: Relevance
“…The nutritive value of leaf protein concentrates from M. sativa has been investigated earlier in other laboratories with higher animals. Thus, Cowlishaw, Eyles, Raymond & Tilley (1956) and Ferrando (1969) found that this species contains toxic substances that lower the nutritive value but which can be removed by washing and heating. It is interesting that this species gave low values with the Tetrahymena test as well.…”
Section: Nutritive Valuementioning
confidence: 99%
“…The nutritive value of leaf protein concentrates from M. sativa has been investigated earlier in other laboratories with higher animals. Thus, Cowlishaw, Eyles, Raymond & Tilley (1956) and Ferrando (1969) found that this species contains toxic substances that lower the nutritive value but which can be removed by washing and heating. It is interesting that this species gave low values with the Tetrahymena test as well.…”
Section: Nutritive Valuementioning
confidence: 99%
“…This juice can either be fed directly or heated to precipitate a protein-rich coagulum, which is filtered off and fed, either wet or after drying. Results of feeding experiments with the coagulated proteins have been reported (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Other data are presented on the chemical compositions of some of the fractions prepared. PROCESSING FRESH ALFALFA tO Separate nonfibrous from fibrous matter has been studied in a number of laboratories (7,4,6,8). These studies and some on other herbage (4,6) have shown that a material of high nitrogen and low fiber content can be separated by processing methods involving grinding or macerating and then squeezing or pressing the broken tissue to extrude the juice.…”
mentioning
confidence: 99%
“…PROCESSING FRESH ALFALFA tO Separate nonfibrous from fibrous matter has been studied in a number of laboratories (7,4,6,8). These studies and some on other herbage (4,6) have shown that a material of high nitrogen and low fiber content can be separated by processing methods involving grinding or macerating and then squeezing or pressing the broken tissue to extrude the juice. Heat treatment of the juice has been reported to yield an insoluble product, high in nitrogen, which with some leaf crops accounts for as much as 50 to 60% of the protein (7).…”
mentioning
confidence: 99%